Police Leadership Development: Intentions and Critical Success-Factors - Jan Ole Vanebo; Brita Bjørkelo; Terje Aaserud (Central European Public Administration Review)
The Norwegian Police Service (NPS) have been heavily criticized after the 22 July 2011 terror attacks at Utøya and in Oslo. One of the evaluation reports stated three shortcomings in the NPS: culture, attitudes and leadership. Management and leadership in the NPS needs to be improved and strengthened, and this shall take place among other things, with the help of a policy document on Civil Service Leadership, elaborated into a manifest called Plattform for medarbeiderskap (Platform of Employeeship for the NPS). The policy document pertains to how the public sector in general ought to be managed, and the document is based on leadership research and is in accordance with mainstream management theory. The idea of formulating a principle of management that would characterize the classical contributions is also evident in this document. This paper addresses two problems: How can value-based police leadership skills be operationalized and measured, and what are the key critical factors in transferring value-based police leadership principles into improved leadership practices?